Dynamics of salt intrusion in complex estuarine networks: an idealised model applied to the Rhine–Meuse Delta - B. Biemond; W. M. Kranenburg; W. M. Kranenburg; Y. Huismans; Y. Huismans; H. E. de Swart; H. A. Dijkstra (Ocean Science)
Many deltas in the world consist of a network of connected channels. We identify and quantify the characteristics of salt intrusion in such systems using an idealised model. The Rhine–Meuse Delta is selected as a prototype example of a complex network with many channels. The model is able to capture the characteristics of the tide-dominated water level variations due to the main tidal component and the salinity time series for 1 year of observations. Quantification of tidally averaged salt transport components shows that transport related to exchange flow is dominant in the seaward, deep parts of the network, but tidal dispersion is dominant in shallower channels further inland. Close to the network junctions, a tidally averaged downgradient salt transport is generated by the tidal currents, which is explained by the phase differences between the tidal currents in the different channels. Salt overspill is confined to the most seaward part of the Rhine–Meuse Delta. The magnitudes of the response times of different channels to changes in discharge increase with the distance to the estuary mouth and with decreasing net water transport through the channel. In channels without a subtidal discharge, response times are a factor of 2–4 larger than in the other channels. The effect of changes in the depth on the extent of salt intrusion strongly depends on where the change takes place. If the change is within the salt intrusion range, deepening will locally increase salt intrusion due to an increase in salt transport by the exchange flow. If the change is outside the salt intrusion range, changes to the net water transport dominate the response of the salt intrusion.